SAKA: ADEQUATE COMPENSATION FOR ORANG ASLI NATIVE LAND - Anuar Alias; Md. Nasir Daud (Penerbit UTHM, 2012)
This book highlights the challenges confronting the Orang Asli in their struggle to secure recognition for their natural rights over native lands and thus for their rights to a more equitable compensation following any compulsory acquisition of those lands. It seeks to present a case for the establishment of a proper and guided compensation framework. Since no empirical study has been conducted to examine issues affecting the acquisition and compensation of Orang Asli native lands before, this book is the first to offer such data. Its contribution is particularly significant to the government agencies interesting their search for uniformity of approach to the assessment of compensation for Orang Asli native lands. Additionally, decision-makers will find in the book a useful source of reference for organising the process and negotiation for compensation in ways that avoid conflicts and create a win-win situation for both the Orang Asli and acquiring body. Finally, this book also serves to inform the academics and practitioners seeking to broaden their perspectives on issues affecting land acquisition of Orang Asli native lands.